2019
DOI: 10.3390/colloids3010017
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Nanocomposites of Iron–Oxide Nanoparticles (IONPs) Synthesized Using Terminalia chebula Leaf Extract for Enhanced Adsorption of Arsenic(V) from Water

Abstract: This study demonstrates the ecofriendly synthesis of iron-oxide nanoparticles (IONPs) and their stabilization with polymers, i.e., chitosan (C) and polyvinyl alcohol (PVA)-alginate (PA), along with a further investigation for the removal of arsenic(As(V)) from water. IONPs with an average diameter of less than 100 nm were prepared via a green synthesis process using an aqueous leaf extract of Terminalia chebula. Batch experiments were conducted to compare the removal efficiency of As(V) by these adsorbents. Fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 66 publications
(88 reference statements)
2
18
0
Order By: Relevance
“…More so, the presence of a small background hump at 2θ range 20°–30° could be assigned to bacterial organic biomolecules associated with the NPs, which was frequently observed in green protocols and also reflected the successful functionalization with metal/metal oxides. That was supported by FT-IR as described below 6 , 23 , 32 .…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…More so, the presence of a small background hump at 2θ range 20°–30° could be assigned to bacterial organic biomolecules associated with the NPs, which was frequently observed in green protocols and also reflected the successful functionalization with metal/metal oxides. That was supported by FT-IR as described below 6 , 23 , 32 .…”
Section: Resultsmentioning
confidence: 65%
“…As a general observation, the sharp and distinct peaks in XRD diffractograms revealed the crystalline nature of biosynthesized NPs with the lowest surface energy 22 . However, other biologically or even chemically synthesized NPs signified the production of imperfect crystals or amorphous phase 9 , 23 . The diffractogram of FCNPs showed characteristic peaks at 2θ = 30.9°, 39.42°, 44.82°, 53.53°, and 68.38° which correspond to (110), (111), (− 202), (020), and (200), Bragg’s reflection, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…It is widely cultivated in different regions of Asia and native to Pakistan, while it is the least researched plants [30,31]. Hence, in continuation of our research being carried out by our group [32][33][34][35][36], in the present study, we have demonstrated the synthesis of CuO NPs using a solution combustion method using the leaf extract of P. emblica as fuel, which is a green alternative to synthetic-organic-compounds-based fuel such as glycine, urea, carboxymethylcellulose, DL-malic acid [37,38]. The synthesized nanoparticles were characterized by different techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The magnetic properties make their recovery very easy at the end of the reaction, and they are recyclable and lower in cost. In general, IONPs exists in various forms (magnetite, maghemite, and hematite) [229][230][231] which are commonly used for the remediation of heavy metals from wastewater. These IONPs remediate heavy metals by adsorption techniques, which is one of the most effective techniques in comparison to precipitation [232,233], coagulation [232][233][234], chemical reduction [235,236], ion exchange [235,237,238] and low expenditure.…”
Section: Role Of Nanotechnology: Nano Adsorbents For Heavy Metal Removalmentioning
confidence: 99%